PROVENANCES AND SEDIMENTATION SETTINGS OF THE VENDIAN TERRIGENIC ROCKS OF THE SOUTHERN PART OF NEPA-BOTUOBA ANTECLISE (SIBERIAN PLATFORM) - Z. L. Motova; A. V. Plyusnin (Геодинамика и тектонофизика)
This paper presents the results of petrographic, lithogeochemical, and U-Pb geochronological studies of detrital zircons in deep core sediments from the Vendian terrigenous sequences of the Nepa and Tira formations in the interior of the Siberian Platform. The section of the Nepa formation is characterized by a terrigenous sediment, the Tira Formation is composed mainly of carbonate rocks. The terrigenous rocks of the Nepa formation are composed of ill-sorted and poorly rounded clasts. Towards the higher part of the section of the Tira formation, there is observed an increase in the degree of sorting and roundness of detrital grains. It has been established that clastic rocks of the lower Nepа subformation are the products derived from rocks of mixed (acidic, basic) composition. The terrigenous rocks of the upper Nepa Subformation and the Tira formation accumulated mainly due to acid decomposition of rocks. The U-Pb (LA-ICP-MS) geochronological studies of detrital zircons from terrigenous rocks of the Nepa and Tira formations led to the conclusion that the sedimentary basin of these formations was contributred to by both the Archean-Early Proterozoic rocks in the basement of the Siberian Platform and the adjacent areas of the Central Asian foldbelt. It is assumed that the sediments of the lower Nepa subformation deposited in the residual basin, formed by joining of terrains and island arcs in the Paleoasian Ocean to the southern margin of the Siberian Platform during the Vendian accretionary-collisional events. This was followed by a transformation into a peripheral sedimentary basin and an occurrence of a transgression of the sea, which favored the accumulation of terrigenous-carbonate rocks of the Tira formation.